Differential accumulation of U14 snoRNA and hsc70 mRNA in Chinese hamster cells after exposure to various stress conditions - Chen, Ming-Shun (Cell Stress Society International, 2002)
We have previously characterized the unique organization of the U14 small nucleolar ribonucleic acid (snoRNA) gene in Chinese hamster HA-1 cells. The single copy of the hsc70/U14 gene is the only source for the production of both U14 snoRNA species and hsc70 messenger ribonucleic acid (mRNA) in these cells. Here we report that the accumulations of U14 snoRNA and hsc70 mRNA are different in response to various stress conditions, although both of them are transcribed in a single primary transcript. Heat shock induced an increased accumulation of both U14 snoRNA and hsc70 mRNA. On the other hand, exposure to sodium arsenite or azetidine induced an increased accumulation of hsc70 mRNA, but did not lead to a concomitant increase in the level of U14 snoRNA. Under normal growth conditions, the variations in the levels of U14 snoRNA and hsc70 mRNA, in the different phases of the cell cycle, are correlated. The increased expression of U14 snoRNA and hsc70 mRNA, and the hsc70 protein induced specifically by heat shock suggest that they participate in the repair process of heat-induced damage to macromolecular complexes involved in the synthesis and processing of ribosomal RNA.